Hypertension and its associated factors in Hosanna town, Southern Ethiopia: community based cross-sectional study - Asfaw, Likawunt Samuel (BMC Res Notes, 2018)
OBJECTIVES: This study was conducted to determine the prevalence of hypertension and its associated factors among residents of Hosanna town in Hadiya Zone. RESULTS: The overall prevalence of hypertension was 30% among the study participants. Out of the study participants who were identified as being hypertensive, only 24.6% knew their hypertensive status. The odds of being hypertensive is significantly higher among males when compared to females (adjusted odds ratio (AOR) 1.9, confidence interval (CI) 1.14–3.23) and married participants as compared to their unmarried counterparts (AOR 4.1; CI 1.10–16.18). High prevalence and increased risks for hypertension were noted among the study participants in the study area. The experiences of aerobic physical activities were reported only in 22.9% of the study participants. These evidences may suggest the need for urgent interventions.